Comment on "An Investigation into the Performance of Particle Swarm Optimization with Various Chaotic Maps". (8th April 2015) - Zhang, Yudong; Ji, Genlin; Dong, Zhengchao; Wang, Shuihua; Phillips, Preetha
Abstract : This paper researched three definitions of Gauss map and found that the definition of "Gauss map" in the paper of Arasomwan and Adewumi may be incoherent with other publications. In addition, we analyzed the difference of continuous Gauss map and the floating-point Gauss map, and we pointed out that the floating-point simulation behaved significantly differently from the continuous Gauss map.